Better Understanding the Climacteric and Menopause Symptoms - Mello, Josiane Medeiros de (2008)
The climacteric and menopause processes are very important in the life of women and, unfortunately, most only manifest any interest on the subject when the first symptoms start to appear, which may vary from organism to organism. To alleviate the discomfort caused by the climacteric and menopause, it is important to initially understand them. Therefore, this study has the main objective of disclosing information concerning the phenomenon involving the climacteric and menopause, besides comparing these two phenomena in a woman that practices hormone replacement therapy and another that do not. This study was carried out using the case report of two women who were interviewed, aged 53 and 52 years. The first had been undergoing hormone replacement treatment, whereas the other had never done it. Data collection was carried out through a recorded and transcribed interview, based on an objective questionnaire and spontaneous reports that took 60 min approximately. The results demonstrated that both women interviewed presented some of the common characteristic symptoms of this period such as heat waves, pain all over the body and changes in humor. As well as that, the woman that had never undergone hormone replacement therapy reported hypertension and changes in sleeping patterns. It is important to highlight that there are processes that can help to delay many of the menopause symptoms, among them hormone replacement when done adequately under medical supervision, as well as the maintenance of a healthy life style.